How Performance of Jakarta Islamic Index (JII) Stocks Relative to Other Stocks? - Listyaningsih, Erna; Krishnamurti, Chandrasekhar (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2015)
This study was conducted to assess the performance of Jakarta Islamic Index (JII) stocks and also investigate whether there was an ethical effect (JII selection restriction) and compare it with non-Sharia stocks. The main model used in this study was the Capital Asset Pricing Model (CAPM) single index model extended to the Fama and French three factors. This study employs elaborate matching data. The data used in this study was split into two periods: the 2005-2007 periods which consists of two groups: JII and non-JII and the 2008-2012 periods which consists of three groups: JII, Sharia and non-Sharia based on industry sector. This study found that basically there was no difference on performance between JII and non-JII stocks. Therefore, this result supports the previous studies in which there were no significant differences between Sharia and conventional investment.